An assessment of present-day crustal deformation in the Kumaun Himalaya from GPS observations - M.Ponraj, S.Amirtharaj; P.S.Sunila, Ajish P.Saji; K.Vijay Kumar, S.K.Arora; C.D. Reddy, S.K.Begum (My University, 2019)
The India-Eurasia collision has created high mountains in the Himalayan plate boundary system, which has led to numerous earthquakes in this region and released part of the elastic strain accumulated over years. In this study, the present-day deformation pattern is derived from geodetic mode Global Positioning System (GPS) measurements obtained during 2005–2016 from 16 campaign sites in the Kumaun province of the central Himalaya. GPS derived horizontal velocity vectors are in the range of 1–9 mm/yr and 27–38 mm/yr with respect to stable India and Eurasia reference frames respectively. To understand the interseismic strain partitioning in the study region, we consider the uniform slip dislocation model over the fault in an elastic, isotropic and homogeneous half-space medium. The model indicates the Main Himalayan Thrust (MHT) fault is locked to a depth of ∼20 km and slips at a rate of 17.2 ± 1 mm/yr with a dip angle of ∼7°. This MHT slip rate build-up corresponds to a moment deficit of 8.4 ± 1 × 1018 Nm/yr due to locking of the fault beneath the Kumaun Himalaya. The total seismic strain accumulation of 61 × 10−6 estimated from the geodetic data suggests the possibility of large earthquakes (typically magnitude 8 and above) with the recurrence interval of around 600 years in the Kumaun Himalayan region.
Keywords: Kumaun Himalaya; Deformation; GPS observations